The Influence of Peer Association and Learning Interest Through Educational Media on Student Learning - Nurqotimah, Siti Nurqotimah; Setiawan, Agus; Anwar, M.Saidun; Anggraeni, Aulia Dita (Delta-Phi: Jurnal Pendidikan Matematika, 2024)
This research focuses on the unsatisfactory learning outcomes of students in mathematics and aims to explore the relationship between peer association, learning interest, and educational media use on students' performance. Employing an experimental method with a mixed-methods approach, the study involves 55 students from classes VIIa and VIIb, with a sample of 30 students selected through random sampling. Data were collected through observations, interviews, questionnaires, documentation, and the application of interactive educational media during math lessons. Using ANCOVA for analysis, the study found that educational media significantly enhances the positive relationship between peer association and learning outcomes. Additionally, learning interest, especially when supported by engaging media, correlates strongly with improved outcomes. Overall, peer association, learning interest, and educational media collectively have a significant and positive impact on student performance.